A Novel [Fe(acac)3] Interspersed g‐C3N4 Heterostructure for Environmentally Benign Visible‐Light‐Driven Oxidation of Alcohols. Issue 44 (22nd November 2018) - Devi, Meghali; Ganguly, Sreejeeb; Bhuyan, Bishal; Dhar, Siddhartha Sankar; Vadivel, Sethumathavan
Abstract : The present work describes facile synthesis of a novel Fe(acac)3 decorated g‐C3 N4 heterostructure. Mixing of iron(III) complex with g‐C3 N4 thorough simple ultrasonication leads to the formation of the heterostructure. The material was thoroughly characterized by FT‐IR, powder XRD, SEM, TEM, UV/Vis DRS and XPS analysis. The analytical results clearly indicate that the Fe III complex is uniformly interspersed with g‐C3 N4 . The results also suggest that there exists synergy between two components in the heterostructure for enhance catalytic performance. This novel material was used as heterogeneous catalyst for visible light driven oxidation of a number of alcohols by H2 O2 . The best ratio of the Fe(acac)3 and g‐C3 N4 is determined with PL analysis. Cold LED light was used as source of visible light. Metal complex decorated g‐C3 N4 heterostructured materials have been rarely used as catalysts for synthetically useful organic transformations. Thus present work on the use of this materials promises to open up new avenues in future growth in metal complex‐graphitic nitride based heterostructure nanocatalysis. Abstract : [Fe(acac)3 ] interspersed g‐C3 N4 heterostructure for environmentally benign visible light promoted oxidation of benzylic and alicyclic alcohols using H2 O2 as oxidant